Inheritance and redistribution: exploring the constitutional commitment towards redistribution in the private law of succession - Cogger, Jonathan (Department of Public Law, 2021)
The inevitability of the death of all property owners means that the redistribution of property at death is a basic function of the law of succession. In the systems that recognise testamentary freedom (including South Africa), the right to distribute property after death is considered as a natural extension of the entitlements that an owner enjoys while alive. Testamentary freedom is an age-old common law principle that has formed part of our law since time immemorial. This right vests in individual owners, and courts (and functionaries of the state) are obliged to give effect to the clear intentions of testators as expressed in their wills. Ownership therefore forms the basis of the right to make testamentary disposals that become enforceable after death. In this way, a primary role of testate succession law is to extend the rights of owners after death. The question this thesis seeks to answer is whether the common law right to dispose of property after death is a constitutionally protected property right in light of constitutional commitments to redistribution, restitution and historical redress. This involves an interpretation of the nature, purpose and scope of section 25 of the Constitution in the context of the common law of testate succession. In this thesis, I critique the academic and judicial view that ownership is central to the constitutional protection of the common law principle of freedom of testation. I argue that the current interpretation of the property clause represents a one-dimensional view of property rights that ignores accepted constitutional property jurisprudence of the interpretive approach to the property clause, including its dual purpose in protecting as well as transforming property relations and the emphasis on our historical context of past discrimination. In essence, my thesis is a critical evaluation of the nature and scope of testamentary freedom for the purposes of justifying the redistribution of wealth and property at death. My ultimate goal is to show that the redistribution of property through inheritance law is politically and constitutionally justified.